Palivizumab's real-world effectiveness: a population-based study in Ontario, Canada, 1993–2017. Issue 2 (28th August 2020) - Fitzpatrick, Tiffany; McNally, James Dayre; Stukel, Therese A; Kwong, Jeffrey C; Wilton, Andrew S; Fisman, David; Guttmann, Astrid
Abstract : Objective: To evaluate the effectiveness of two palivizumab programmes targeting high-risk infants, defined by prematurity, diagnosis of comorbidities and geography, and assess potential disparities by neighbourhood income. Design: Controlled, interrupted time series. Setting: Ontario, Canada. Patients: We used linked health and demographic administrative databases to identify all children born in hospitals 1 January 1993 through 31 December 2016. Follow-up ended at the earliest of second birthday or 30 June 2017. Intervention: Palivizumab-eligibility: child was born very preterm and ≤6 months old during respiratory syncytial virus (RSV) season; <24 months old with significant chronic lung or congenital heart disease; or ≤6 months, born preterm or residents of remote regions. Main outcome: Severe RSV-related illness, defined as hospitalisation or death with a diagnosis of bronchiolitis, RSV pneumonia or RSV. Results: 3 million births and 87 000 RSV-related events were identified. Over the study period, rates of severe RSV-related illness declined 65.4% among the highest risk group, eligible infants <6 months (230.6 to 79.8 admissions per 1000 child-years). Relative to changes among ineligible infants <6 months, rates dropped 10.4% (95% CI −18.6% to 39.4%) among eligible infants immediately following introduction of a national palivizumab programme in 1998. Initially, rates were considerably higher among infants from low-income neighbourhoods, but income-specific rates converged over time among eligible infants <6 months; such convergence was not seen among other children. Conclusions: Incidence of severe RSV-related illness declined over the study period. While we cannot attribute causality, the timing and magnitude of these declines suggest impact of palivizumab in reducing RSV burden and diminishing social inequities among palivizumab-eligible infants.